TINJAUAN HUKUM TERHADAP UPAYA MANTAN ISTRI DALAM MEMPERJUANGKAN HAK NAFKAH YANG TIDAK DIPENUHI OLEH MANTAN SUAMI - Ruslan, Dyah Auliah Rachma (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to analyze the efforts of ex-wives in fighting for alimony that has not been fulfilled by their ex-husbands after divorce, as well as the legal review related to this issue. In Indonesian law, the alimony rights for ex-wives are regulated under Law No. 1 of 1974 on Marriage and the Civil Code (KUHPerdata), which stipulates the ex-husband's obligation to provide alimony to the ex-wife who is financially unable to support herself. However, in practice, many ex-wives face difficulties in obtaining this alimony due to non-compliance by the ex-husbands and barriers in the legal procedure. This research uses a qualitative method with an in-depth case study approach, analyzing various challenges faced by ex-wives in fighting for their alimony rights, as well as the legal procedures available. The results show that although the law provides a clear foundation, the implementation of alimony rights still faces many obstacles, including issues of proof, legal costs, and social and economic inequality between the ex-husband and ex-wife. Therefore, it is recommended that the government and legal institutions strengthen the family court system, provide greater access to legal aid, and raise legal awareness among the public. Keywords:  Alimony, Ex-Wife, Divorce, Alimony Rights, Family Law, Legal Procedures.